Physiological and Molecular Study of Iraqi Women with Polycystic Ovary Syndrome (Medico Legal Update, 2021)
Polycystic ovary syndrome is define as illness in women that a reproductive age because commonendocrinopathy and lead to reproductive dysfunction also infertility. PCOS is usually alignment withinsulin resistance and metabolic syndrome, it is think that PCOS is the outcome of genetic effect additionto ecological factor. In this study (100) samples which divided into 40 samples of heath women and 60samples of women with PCOS. It diagnosed by ovarian morphology on ultrasound also test the fasting bloodsugar, insulin, insulin resistance and testosterone hormone by biochemical method also used molecularmethod to detect the genotype of TCF4 gene (rs290487) by RFLP-PCR technique. The results revealed thatthe frequency of allele T was recorded a highly significance (P